Comparative Study on Antioxidant Activities of Black and White Seed Varieties of Cow Hedge Mucuna pruriens L - Alagu Lakshmanan, Ganapathy M (International Journal of Pharmaceutical & Biological Archive, 2012)
Comparative Study on Antioxidant Activities of Black and White Seed Varieties of Cow Hedge Mucuna pruriens L